FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU SEKSUAL MURID SMU NEGERI DI KOTA PADANG TAHUN 2007 - Dien GA Nursal (Faculty of Public Health, Andalas University, 2008)
Adolescent marked with the unbalance physical and mental growth which is followed by behaviorally trying something often plung into sex before mariage, adolescent pregnancy, unsave abortion, infection STD and HIV/AIDS and drugs. The research is to know the sexual behavior of students at State Senior High School in Padang and factors that related. This research use the cross sectional method with 350 responder taken by multistage systematic random sampling and analysed with univariat, bivariate and multivariat. The result shown that 16,6% responder have the risky heavy sexual behavior. Mostly responder is women, puberty at normal age, have negatif attitude, do not have the active communications with its parents (64,9%) and friends (52,6%), have both parents (91,1%), democration parenting styles (49,9%) and have access to the electronic media and media print. Knowledge is equal between lower and higher and only small responder have boyfriend/girlfriend more than 3 times and meeting with the boyfiend/girlfriend less than 5 hour/week and more than 21 hour/week. At bivariate analysis found that gender, puberty age, knowledge, attitude, parents’ marriage status, parenting style, amount and meeting duration with boyfriend/girlfriend, electronic media and printing media have significantly relation with adolescent sexual behavior. At multivariate analysis found that gender, knowledge, parenting style and amount of boyfriend/girlfriend together influence the sexual behavior. From this research suggested for the increase students’ knowledge and performing seminar for parents, limit the pornography spreading through the television and porn magazine/book, accomodating and giving consultancy concerning about puberty early, risky sexual behavior and knowledge about sex health.